2002
DOI: 10.4049/jimmunol.169.4.1829
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Driven Oligoclonal Expansion of Tumor-Infiltrating B Cells in Infiltrating Ductal Carcinoma of the Breast

Abstract: The objective of this study was to determine whether tumor-infiltrating B cells (TIL-B) of infiltrating ductal carcinoma (IDC) of the breast represent a tumor-specific humoral immune response. Immunohistochemical analysis of three Her-2/neu-negative IDC tumors from geriatric patients showed that TIL-B cluster in structures similar to germinal centers containing CD20+ B lymphocyte and CD3+ T lymphocyte zones with interdigitating CD21+ follicular dendritic cells, suggesting an in situ immune response. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
124
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 40 publications
15
124
1
2
Order By: Relevance
“…Restricted Ig gene expression in TIL-Bs has been described by others (36,37). Some investigators have suggested that this expansion occurs within the tumor tissue and in tumor-associated germinal centers (36). By contrast, our result shed light to another option where a tumor-draining LN could be the origin of the B cell response in our study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Restricted Ig gene expression in TIL-Bs has been described by others (36,37). Some investigators have suggested that this expansion occurs within the tumor tissue and in tumor-associated germinal centers (36). By contrast, our result shed light to another option where a tumor-draining LN could be the origin of the B cell response in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…8). Restricted Ig gene expression in TIL-Bs has been described by others (36,37). Some investigators have suggested that this expansion occurs within the tumor tissue and in tumor-associated germinal centers (36).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the infiltrating B cells in different types of cancers are clonal and express immunoglobulins that originate from a dominant germ line gene (47)(48)(49). Here, a tumor antigen, as opposed to a transplantation antigen, may drive the infiltrating cells and possibly tumor-specific mechanisms of local "immunosuppression" are also operant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the improved clinical outcome is due at least in part to the presence of prominent lymphocyte infiltrates in the tumor. [7][8][9][10][11] In contrast, invasive micropapillary carcinoma has a high incidence of axillary lymph node metastasis and poor prognosis and the mechanism is still poorly understood. In our previous study, 4 we found that invasive micropapillary carcinoma rich in tumor infiltrating lymphocytes was associated with an increased incidence of lymph node metastasis and an increased number of positive lymph nodes per case.…”
Section: Discussionmentioning
confidence: 99%